2018
DOI: 10.1142/s021987621850055x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Time Delayed SIR Epidemic Model Along with Nonlinear Incidence Rate and Holling Type-II Treatment Rate

Abstract: In this paper, we present a mathematical study of a deterministic model for the transmission and control of epidemics. The incidence rate of susceptible being infected is very crucial in the spread of disease. The delay in the incidence rate is proved fatal. In the present study, we propose an SIR mathematical model with the delay in the infected population. We are taking nonlinear incidence rate for epidemics along with Holling type II treatment rate for understanding the dynamics of the epidemics. Model stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Our analysis showed that when R 0 ≤ 1, the disease-free equilibrium is globally asymptotically stable, and when R 0 > 1, then there is a unique disease-endemic equilibrium, which is globally asymptotically stable. To put this result in context, we chose the treatment function T(I) = aI(t) 1+ξ I(t) (see [23]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis showed that when R 0 ≤ 1, the disease-free equilibrium is globally asymptotically stable, and when R 0 > 1, then there is a unique disease-endemic equilibrium, which is globally asymptotically stable. To put this result in context, we chose the treatment function T(I) = aI(t) 1+ξ I(t) (see [23]).…”
Section: Resultsmentioning
confidence: 99%
“…where a represents the maximal medical resources supplied per united time and is half-saturation constant, which measures the effect of being delayed for treatment. Other works have investigated the effects of the treatment on an epidemic (see [19][20][21][22][23][24][25]) and also its optimal control (see [26]). The motivation of this work comes from [10,11], where the authors studied an SIR epidemic model with nonlinear incidence function, and from [19][20][21], where the authors considered a special type of treatment function.…”
Section: Introductionmentioning
confidence: 99%
“…To control or remove a disease, complete understanding of the dynamics of its progression is required. Based on the observed characteristics of infectious diseases, epidemiologists [1][2][3][4][5][6][7][8][9][10][11][12][13] have attempted to construct mathematical models that make it possible to understand various aspects of many diseases and suggest methods for their control. A crucial issue in the study of the spread of an infectious disease is how it is transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore a need to modify the classical linear incidence rate in order to study the dynamics of infection among a large population. Many researchers [2][3][4][5]7,10,11,[15][16][17][18] have proposed transmission laws that include nonlinearity, such as the Holling type II functional, Crowley-Martin functional, Beddington-DeAngelis functional, etc., to study the dynamics of infectious diseases. The general incidence rate g(I )S = k I p S 1 + α I q , was suggested by Liu et al [19] and used by numerous authors in their models (see, for example, [9,15,[20][21][22]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation